2014
DOI: 10.1152/ajpgi.00383.2013
|View full text |Cite
|
Sign up to set email alerts
|

Xenin-25 delays gastric emptying and reduces postprandial glucose levels in humans with and without Type 2 diabetes

Abstract: Xenin-25 (Xen) is a neurotensin-related peptide secreted by a subset of glucose-dependent insulinotropic polypeptide (GIP)-producing enteroendocrine cells. In animals, Xen regulates gastrointestinal function and glucose homeostasis, typically by initiating neural relays. However, little is known about Xen action in humans. This study determines whether exogenously administered Xen modulates gastric emptying and/or insulin secretion rates (ISRs) following meal ingestion. Fasted subjects with normal (NGT) or imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 58 publications
4
45
0
Order By: Relevance
“…More encouraging, recent studies have highlighted the possibility that xenin, a hormone co-secreted with GIP from a subset of enteroendocrine K cells, could amplify the insulin-secretory response of GIP [9]. In agreement, observations from our laboratory and others confirm the GIP-potentiating effects of xenin under normal and type 2 diabetes conditions [10][11][12][13]. Furthermore, there is also evidence to suggest that xenin acts as a satiety hormone in animals [10,[14][15][16][17] and humans [18].…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…More encouraging, recent studies have highlighted the possibility that xenin, a hormone co-secreted with GIP from a subset of enteroendocrine K cells, could amplify the insulin-secretory response of GIP [9]. In agreement, observations from our laboratory and others confirm the GIP-potentiating effects of xenin under normal and type 2 diabetes conditions [10][11][12][13]. Furthermore, there is also evidence to suggest that xenin acts as a satiety hormone in animals [10,[14][15][16][17] and humans [18].…”
Section: Introductionsupporting
confidence: 83%
“…For GIP, the first 14 N-terminal amino acid residues contain the bioactive domain important for insulin-secretory function [25,26]. Based on this knowledge, we constructed a novel GIP/xenin hybrid peptide, (DAla 2 )GIP/xenin-8-Gln, by linking GIP (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) to xenin-8-Gln, retaining the regions of each peptide known to be important for biological activity (see electronic supplementary material [ESM] Table 1). Importantly, since GIP is a substrate for dipeptidyl peptidase-4 (DPP-4) [27], the hybrid peptide includes substitution of the naturally occurring alanine L isomer residue by a D isomer at position 2 [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…However, co-treatment with recombinant xenin-25 and GIP reduces postprandial glycemia by delaying gastric emptying in humans with or without type 2 diabetes (15). Thus, while GIP is considered an incretin hormone, its mechanisms of action and its significance in glucoregulation remain to be fully understood.…”
Section: Intestine To Beta Cell Communicationmentioning
confidence: 99%
“…In human studies, our laboratory has shown that intravenous administration of Xen amplified the effects of GIP on insulin, glucagon, and pancreatic polypeptide release during graded glucose infusions [17,18]. During liquid mixed meal tolerance tests, Xen infusion delayed gastric emptying, reduced postprandial glycemia, and inhibited glucagon-like peptide-1 (GLP-1) release and insulin secretion [19]. Importantly, the reduced insulin secretion was a consequence of lower glucose levels and not an inhibition of insulin release per se.…”
Section: Introductionmentioning
confidence: 99%